Heterozygous variants in the DVL2 interaction region of DACT1 cause CAKUT and features of Townes-Brocks syndrome 2 - Christians, Anne; Kesdiren, Esra; Hennies, Imke; Hofmann, Alejandro; Trowe, Mark-Oliver; Brand, Frank; Martens, Helge; Gjerstad, Ann Christin; Gucev, Zoran; Zirngibl, Matthias; Geffers, Robert; Seeman, Tomáš; et al. (Human genetics, 2023)
Most patients with congenital anomalies of the kidney and urinary tract (CAKUT) remain genetically unexplained. In search of novel genes associated with CAKUT in humans, we applied whole-exome sequencing in a patient with kidney, anorectal, spinal, and brain anomalies, and identified a rare heterozygous missense variant in the DACT1 (dishevelled binding antagonist of beta catenin 1) gene encoding a cytoplasmic WNT signaling mediator. Our patient's features overlapped Townes-Brocks syndrome 2 (TBS2) previously described in a family carrying a DACT1 nonsense variant as well as those of Dact1-deficient mice. Therefore, we assessed the role of DACT1 in CAKUT pathogenesis. Taken together, very rare (minor allele frequency ≤ 0.0005) non-silent DACT1 variants were detected in eight of 209 (3.8%) CAKUT families, significantly more frequently than in controls (1.7%). All seven different DACT1 missense variants, predominantly likely pathogenic and exclusively maternally inherited, were located in the interaction region with DVL2 (dishevelled segment polarity protein 2), and biochemical characterization revealed reduced binding of mutant DACT1 to DVL2. Patients carrying DACT1 variants presented with kidney agenesis, duplex or (multi)cystic (hypo)dysplastic kidneys with hydronephrosis and TBS2 features. During murine development, Dact1 was expressed in organs affected by anomalies in patients with DACT1 variants, including the kidney, anal canal, vertebrae, and brain. In a branching morphogenesis assay, tubule formation was impaired in CRISPR/Cas9-induced Dact1-/- murine inner medullary collecting duct cells. In summary, we provide evidence that heterozygous hypomorphic DACT1 variants cause CAKUT and other features of TBS2, including anomalies of the skeleton, brain, distal digestive and genital tract.
Keywords: adaptorové proteiny signální transdukční; Animals; Kidney; Nuclear Proteins; močové ústrojí; Humans; lidé; zvířata; Mice; protein dishevelled; ledviny; urogenitální abnormality; jaderné proteiny; Urogenital Abnormalities; Adaptor Proteins, Signal Transducing; Dishevelled Proteins; Urinary Tract; myši